Differences in ​the proportion of children meeting behavior guidelines ​between summer ​and school by socioeconomic status and race - Ethan T. Hunt; Lauren vonKlinggraeff; Alexis Jones; Sarah Burkart; Rodrick Dugger; Bridget Armstrong; Michael W. Beets; Gabrielle Turner‐McGrievy; Marco Geraci; R. Glenn Weaver (Wiley, 2021)
Abstract Objective Children who fail to meet activity, sleep, and screen‐time guidelines are at increased risk for obesity. Further, children who are Black are more likely to have obesity when compared to children who are White, and children from low‐income households are at increased risk for obesity when compared to children from higher‐income households. The objective of this study was to evaluate the proportion of days meeting obesogenic behavior guidelines during the school year compared to summer vacation by race and free/reduced priced lunch (FRPL) eligibility. Methods Mixed‐effects linear and logistic regressions estimated the proportion of days participants met activity, sleep, and screen‐time guidelines during summer and school by race and FRPL eligibility within an observational cohort sample. Results Children (n = 268, grades = K − 4, 44.1%FRPL, 59.0% Black) attending three schools participated. Children's activity, sleep, and screen‐time were collected during an average of 23 school days and 16 days during summer vacation. During school, both children who were White and eligible for FRPL met activity, sleep, and screen‐time guidelines on a greater proportion of days when compared to their Black and non‐eligible counterparts. Significant differences in changes from school to summer in the proportion of days children met activity (−6.2%, 95CI = −10.1%, −2.3%; OR = 0.7, 95CI = 0.6, 0.9) and sleep (7.6%, 95CI = 2.9%, 12.4%; OR = 2.1, 95CI = 1.4, 3.0) guidelines between children who were Black and White were observed. Differences in changes in activity (−8.5%, 95CI = −4.9%, −12.1%; OR = 1.5, 95CI = 1.3, 1.8) were observed between children eligible versus uneligible for FRPL. Conclusions Summer vacation may be an important time for targeting activity and screen‐time of children who are Black and/or eligible for FRPL.